2017
DOI: 10.1002/ijc.31116
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence in adults living in the vicinity of nuclear power plants in France, based on data from the French Network of Cancer Registries

Abstract: Nuclear power plants (NPPs) release toxic emissions into the environment that may affect neighboring populations. This ecologic study was designed to investigate the possibility of an excess incidence of cancer in the vicinity of French NPPs by examining the incidence by municipality of 12 types of cancer in the population aged 15 years and older during the 1995-2011 period. Population exposure to pollution was estimated on the basis of distance from towns of residence to the NPP. Using regression models, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…Nuclear power plants are a source of radiation and chemical contaminants; the exposure of which are known risk factors for many cancers. Some studies shown association between radiation and risk of leukaemia cancer among adult and childhood [10][11][12]. In our study, cancer incidence rate for leukaemia is 4.5 (per lac) in Kalpakkam, followed by 3.1 in Kudankulam, 1.4 in Karwar, 1.8 in Palghar, 1.2 in Kakrapar and 0.6 in Rawatbhata among male population; similarly, in female rates are 3.1 in Kalpakkam, 2.2 in Kudankulam, 1.8 in Palghar, 1.5 in Rawatbhata, 1.0 in Kakrapar and 0.9 in Karwar NPP registries.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear power plants are a source of radiation and chemical contaminants; the exposure of which are known risk factors for many cancers. Some studies shown association between radiation and risk of leukaemia cancer among adult and childhood [10][11][12]. In our study, cancer incidence rate for leukaemia is 4.5 (per lac) in Kalpakkam, followed by 3.1 in Kudankulam, 1.4 in Karwar, 1.8 in Palghar, 1.2 in Kakrapar and 0.6 in Rawatbhata among male population; similarly, in female rates are 3.1 in Kalpakkam, 2.2 in Kudankulam, 1.8 in Palghar, 1.5 in Rawatbhata, 1.0 in Kakrapar and 0.9 in Karwar NPP registries.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid cancer incidence was not different between the group of inhabitants living in the townships where nuclear power plants are located and the “nonplant‐vicinity” group, these groups including 48 and 25 cases, respectively. In France, a significantly lower risk of thyroid cancer was observed in women living in the 20 km proximity area of the seven nuclear power plants under study (RR = 0.86, 95% CI: 0.77;0.96) . The authors suggest that a possible difference in medical practices might explain the results.…”
Section: Discussionmentioning
confidence: 83%
“…In France, a significantly lower risk of thyroid cancer was observed in women living in the 20 km proximity area of the seven nuclear power plants under study (RR = 0.86, 95% CI: 0.77;0.96). 48 The authors suggest that a possible difference in medical practices might explain the results.…”
Section: Discussionmentioning
confidence: 99%
“…An ecologic study [61] found a statistically significant RR of BC in persons living inside 20 km from a nuclear power plant (RRmen 1.08 [95% CI 1.00-1.17], RRwomen 1.19 (95% CI 1.02-1.39]). However, the study used proximity as a proxy for exposure and did not assess blood profiles.…”
Section: Nuclear Power Plant and Shale Gas Extractionmentioning
confidence: 99%